Glucocorticoids enhance chemotherapy-driven stress granule assembly and impair granule dynamics, leading to cell death - Schwed-Gross, Avital; Hamiel, Hila; Faber, Gabriel P; Angel, Mor; Ben-Yishay, Rakefet; Benichou, Jennifer I C; Ishay-Ronen, Dana; Shav-Tal, Yaron (Journal of cell science, 2022)
Stress granules (SGs) can assemble in cancer cells upon chemotoxic stress. Glucocorticoids function during stress responses and are administered with chemotherapies. The roles of glucocorticoids in SG assembly and disassembly pathways are unknown. We examined whether combining glucocorticoids such as cortisone with chemotherapies from the vinca alkaloid family, which dismantle the microtubule network, affects SG assembly and disassembly pathways and influences cell viability in cancer cells and human-derived organoids. Cortisone augmented SG formation when combined with vinorelbine (VRB). Live-cell imaging showed that cortisone increased SG assembly rates but reduced SG clearance rates after stress, by increasing protein residence times within the SGs. Mechanistically, VRB and cortisone signaled through the integrated stress response mediated by eIF2α (also known as EIF2S1), yet induced different kinases, with cortisone activating the GCN2 kinase (also known as EIF2AK4). Cortisone increased VRB-induced cell death and reduced the population of cells trapped in mitotic catastrophe. These effects were mediated by the core SG proteins G3BP1 and G3BP2. In conclusion, glucocorticoids induce SG assembly and cell death when administered with chemotherapies, suggesting that combining glucocorticoids with chemotherapies can enhance cancer cell chemosensitivity.Stress granules (SGs) can assemble in cancer cells upon chemotoxic stress. Glucocorticoids function during stress responses and are administered with chemotherapies. The roles of glucocorticoids in SG assembly and disassembly pathways are unknown. We examined whether combining glucocorticoids such as cortisone with chemotherapies from the vinca alkaloid family, which dismantle the microtubule network, affects SG assembly and disassembly pathways and influences cell viability in cancer cells and human-derived organoids. Cortisone augmented SG formation when combined with vinorelbine (VRB). Live-cell imaging showed that cortisone increased SG assembly rates but reduced SG clearance rates after stress, by increasing protein residence times within the SGs. Mechanistically, VRB and cortisone signaled through the integrated stress response mediated by eIF2α (also known as EIF2S1), yet induced different kinases, with cortisone activating the GCN2 kinase (also known as EIF2AK4). Cortisone increased VRB-induced cell death and reduced the population of cells trapped in mitotic catastrophe. These effects were mediated by the core SG proteins G3BP1 and G3BP2. In conclusion, glucocorticoids induce SG assembly and cell death when administered with chemotherapies, suggesting that combining glucocorticoids with chemotherapies can enhance cancer cell chemosensitivity.